Variação morfológica e molecular da espécie Dendropsophus minutus (Amphibia, Anura, Hylidae) em sua área de ocorrência no Brasil - Melo, Suélen Helena Martins (Universidade Federal de São Carlos, 2019)
Dendropsophus minutus is a widely distributed hyilid in the Neotropical Region that have significant morphological variation along its area of occurrence. Recent molecular studies revealed high diversity of clades under the name Dendropsophus minutus. By this reason, we sought to identify patterns of polymorphisms in Dendropsophus minutus along the species distribution through the different Brazilian phytophysiognomies: Amazon, Caatinga, Cerrado, Atlantic Forest and Pampa. We studied the morphological variation in Dendropsophus minutus by analyzing the morphometry and dorsal color pattern of males housed in Brazilian herpetological collections. Additionally, we amplified the 16S mitochondrial gene fragment to allocate morphometrically analyzed specimens into the phylogenetic tree from the literature. Even though there are sympatrics morphotypes in Dendropsophus minutus, we observe the absence of the dorsal pattern “bivittata” form in Northern Brazil, while the “minuta” pattern was not recorded in the South of the country. This study did not distinguish morphometrically the species through its distribution in Brazil; however, significant molecular differentiation in Amazonian specimens currently identified as Dendropsophus minutus was described, that are strongly related to samples of the taxon Dendropsophus goughi.
Morphological and molecular variation of the species Dendropsophus minutus (Amphibia, Anura, Hylidae) in its area of occurrence in Brazil
Keywords: Anfíbios; Anuros; Morfologia externa; Taxonomia; Filogenia; Variação intraespecífica; Amphibians; Anurans; External morphology; Taxonomy; Phylogeny; Intraspecific variation; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::ZOOLOGIA